Cos((3/2)x)cos(x/2)-1> ((1-sqrt3)/(2))*cosx

Telman07 Telman07    1   28.09.2019 21:10    0

Ответы
nicita13254769p06wrf nicita13254769p06wrf  09.10.2020 01:22

task/29760192     cos(3x/2)*cos(x/2) -1  > (1/2) * (1 -√3) *cosx

Решение :  cos(3x/2)*cos(x/2) -1  > (1/2) * (1 -√3) *cosx     ||*2||

2cos(3x/2)*cos(x/2) -2   >  (1 -√3) *cosx  ;

cos2x+cosx -  (1 -√3) *cosx  - 2   >  0  ;

2cos²x -1 +cosx  -  cosx +(√3) *cosx  - 2   >  0  ;

2cos²x +(√3) *cosx -3 >0 ⇔ ( cosx +√3 )(2cosx -√3 ) >0   ||cosx +√3 >0 ||⇔ cosx  > (√3) /2    ⇒  2πn  - π / 6  < x <  π / 6 + 2πn   , n ∈ ℤ                    (объединение интервалов )   

ответ :  x ∈ ( - π / 6 + 2πn  ;    π / 6 + 2πn  ) , n ∈ ℤ.              

P.S. 2cos²x +(√3) *cosx -3 = 0. D=(√3)²+4*2*(-3) =27 =(3√3)² ⇒√D =3√3)  

cosx₁ = - √3  < - 1 → посторонний корень  ;   cosx₂ =(√3) / 2.    * * *  

ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра

Популярные вопросы